2005
DOI: 10.1056/nejmoa044064
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Medical Management with Misoprostol and Surgical Management for Early Pregnancy Failure

Abstract: Treatment of early pregnancy failure with 800 microg of misoprostol vaginally is a safe and acceptable approach, with a success rate of approximately 84 percent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
220
2
40

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 289 publications
(271 citation statements)
references
References 19 publications
9
220
2
40
Order By: Relevance
“…Miscarriage is the most common gynecological emergency (accounting for 75% of gynecological Emergency Room Visits in the United Kingdom [2]; and two previous studies demonstrated that 15% of patients who miscarry do so spontaneously in the first trimester [3,4]. Approximately one in four women will have an early pregnancy failure during her lifetime [4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Miscarriage is the most common gynecological emergency (accounting for 75% of gynecological Emergency Room Visits in the United Kingdom [2]; and two previous studies demonstrated that 15% of patients who miscarry do so spontaneously in the first trimester [3,4]. Approximately one in four women will have an early pregnancy failure during her lifetime [4].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one in four women will have an early pregnancy failure during her lifetime [4]. Miscarriages in pregnancies achieved by assisted reproductive technology (ART) procedures may be slightly more frequent than in general population and occur in 16% -30% of patients with confirmed pregnancy [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations